On the equation of state and properties of the plasma in underwater discharges - Porytskyy, P.V.; Starchyk, P.D. (Вопросы атомной науки и техники, 2017)
It is considered the peculiarities of the equation of state of plasma in underwater discharges. The transport properties of a nonideal plasma of underwater discharges are calculated at pressure range from 1 bar up to 200 bar. The transport coefficient set based on the Grad’s method is compared with the data obtained by using of the Lorentzian plasma theory at the same plasma composition. Also, the calculation data are considered to be in reference with transport coefficients obtained by using the Chapman-Enskog’ method. It is pointed that the nonideality effects are needed to take into consideration under calculation of properties of underwater discharge. Рассмотрены особенности уравнения состояния для плазмы подводных разрядов. Проведены расчёты транспортных свойств неидеальной плазмы подводных разрядов в диапазоне давлений 1…200 бар. Транспортные коэффициенты, которые рассчитывались на основе метода Грэда, сравниваются с результатами, полученными исходя из лоренцевой теории при одинаковом составе плазмы. Также результаты вычислений сравниваются с данными, полученными методом Чепмена-Энскога. Подчёркивается необходимость принятия во внимание эффектов неидеальности при расчёте свойств подводных разрядов. Розглянуто особливості рівняння стану для плазми підводних розрядів. Проведені розрахунки транспортних властивостей неідеальної плазми підводних розрядів у воді в діапазоні тисків 1…200 бар. Транспортні коефіцієнти, що були розраховані на основі методу Ґреда, порівняно із результатами, які ґрунтувалися на лоренцевій теорії за однакового складу плазми. Також результати обчислень порівнювалися із даними, що отримано за допомогою метода Чепмена-Енскоґа. Наголошено на необхідність взяти до уваги ефекти неідеальності плазми для розрахунку властивостей плазми підводних розрядів.